An exploratory study on the application of screening of activity limitation and safety awareness (SALSA) scale for evaluation of activity limitation among elderly - Roshni Mary Peter; Alex Joseph (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Aging poses a significant risk for activity and functional limitations. Problems among aged populations are interrelated, and these problems can lead to other disorders and finally leave a negative impact on the quality of life (QoL) This study used the screening of activity limitation and safety awareness (SALSA) scale to screen and measure activity limitations among the elderly. MATERIALS AND METHODS: A community-based descriptive cross-sectional study was conducted among 928 elderly from the three districts of Tamil Nadu, India. The SALSA scale was administered via a door-to-door interview, and data analysis was carried out. Simple random sampling was used to obtain the study subjects in the selected study area. Chi-square tests and binary logistic regression were performed to find the association between selected risk factors. RESULTS: Among the 928 elderly, 53.7% of them were males, 84.9% were between the age of 60 and 69 years, and 31% were 70 years and above. The study found that 66.5% of the elderly have mild activity limitations, 15.7% of them had moderate limitations, 4.8% of them had severe limitations, around 3% of them had extreme limitations, and 10.3% of them had no significant limitations. The binary logistic regression found people of age 65 and above (OR = 3.80), female gender (OR = 2.90), with hypertension (OR = 1.95), vision problem (OR = 1.92), decreased sensation of the foot (OR = 3.41), as the significant independent risk factors for activity limitation among the elderly. CONCLUSION: The study found self-reported activity limitations among the elderly to be nearly 90%. The SALSA scale may be used as a handy tool to identify the activity limitation in community-based geriatric checkups.